2020
DOI: 10.3390/ijerph17207504
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Sustainability Commitment and Financial Performance of Firms Listed on the Johannesburg Stock Exchange (JSE)

Abstract: The importance of heeding the environmental sustainability commitment call cannot be underestimated. Laggards in terms of environmental sustainability commitment are likely to face fines and penalties as talks to tighten environmental legislation are now at an advanced stage globally. The current work assessed the link between environmental sustainability commitment and financial performance of firms listed on the Johannesburg Stock Exchange (JSE). The study was quantitative in nature with a case study researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…It was observed that the response to a call for environmental sustainability undertaking regarding compliance and reporting by listed companies is slow and consequently some companies indulge in fraudulent activities as well as greenwashing to get away with environmental commitment (Dzomonda & Fatoki, 2020). Against this backdrop, it was noted that a few companies remain highly environmentally sustainable in comparison with those that are not committed to environmental sustainability (Kiron, Unruh, Kruschwitz, Reeves, Rubel & Felde, 2017).…”
Section: Progress Made By South African Listed Companies On Sustainab...mentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that the response to a call for environmental sustainability undertaking regarding compliance and reporting by listed companies is slow and consequently some companies indulge in fraudulent activities as well as greenwashing to get away with environmental commitment (Dzomonda & Fatoki, 2020). Against this backdrop, it was noted that a few companies remain highly environmentally sustainable in comparison with those that are not committed to environmental sustainability (Kiron, Unruh, Kruschwitz, Reeves, Rubel & Felde, 2017).…”
Section: Progress Made By South African Listed Companies On Sustainab...mentioning
confidence: 99%
“…The lack of standards to ensure uniformity in sustainability reporting leads to some companies cheating as they report on ESG issues. Dzomonda and Fatoki (2020) indicated that some companies indulge in fraudulent activities as they prepare their integrated reports. Some also indulge in greenwashing, a way of marketing their company giving the impression that their company is environmentally friendly.…”
Section: Measuring a Company's Sustainability Is A Challenge Because ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature delves constantly into the factors influencing financial performance and singles out liquidity, working capital (Akgün and Memiş Karataş 2020), corporate governance (Abdo and Fisher 2007;Coleman and Wu 2020) or environmental sustainability commitment (Dzomonda and Fatoki 2020), to mention but a few. For instance, El-Ansary and Al-Gazzar (2020) examined the degree to which net working capital drove company profitability for 134 companies operating in 12 countries from Middle East and North Africa (MENA) during the period 2013-2019.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering the Global South, a lot more progress of businesses towards sustainable development is required within the policy-science spectrum which is gradually growing [22]. For instance, in South Africa, Dzomonda and Fatoki [23] have reported that the Johannesburg Stock Exchange (JSE) now regulates the reporting of listed firms' environmental performance as part of regulatory demands for sustainability reporting, and it is ascertained that firms committed to environmental investment are likely to enhance their environmental performance. Also, Africa's Development Agenda (2063) and the Global Sustainability Agenda (2030) have provided frameworks that can help map the consequences of corporate organizations' commitments and practices against broader socio-environmental goals [24].…”
Section: Setting the Agenda: Sustainability And The Expected Role Of Corporate Entitiesmentioning
confidence: 99%